Peran Guru Tahfidz dalam Meningkatkan Kedisiplinan Hafalan Al-Qur’an pada Siswa - Masithoh, Fisa Bela; Subando, Joko (Lembaga Yasin AlSys, 2026)
This study aimed to analyze the role of tahfidz teachers in enhancing the discipline of Al-Qur’an memorization among students at MTs Negeri 5 Demak. The study emphasizes that tahfidz teachers play multifaceted roles as instructors, motivators, mentors, evaluators, and facilitators who adapt instructional methods to students’ characteristics. Structured learning strategies—including the preparation of regular schedules, the use of varied methods, the implementation of periodic evaluations and continuous monitoring, as well as the provision of intrinsic and extrinsic motivation—serve as key supporting factors in building students’ consistency and commitment in memorizing the Al-Qur’an. The support of the madrasah environment and parents’ involvement further reinforces memorization discipline through the strengthening of a religious culture and layered supervision at school and at home. The findings show that the synergistic interaction among teacher roles, learning strategies, student motivation, and environmental support generates sustainable and high-quality memorization discipline. These results provide theoretical and practical foundations for the development of tahfidz programs in formal madrasah, particularly in designing comprehensive memorization guidance models oriented toward the formation of long-term religious commitment.